Individualized Assignments, Group Work and Discussions: How They Interact With Class Size, Low Socioeconomic Status, and Second Language Learners - DeVries, Jeffrey M.; Szardenings, Carsten; Doebler, Philipp; Gebhardt, Markus (Frontiers in Education, 2020)
Varied teaching techniques are an important aspect of a successful classroom. Student and classroom factors such as ability level, lower socioeconomic status and/or native language can interact with teaching techniques. Previous work suggests that each teaching technique may be more effective for different students or in different classroom situations, but few studies have directly examined which factors relate to effective teaching techniques. This study uses data representative for early secondary school students in Germany from the National Education Panel Study (NEPS) to examine the effects of group work, discussions, and individualized assignments on reading and math competency change between 7th and 9th grade. Additionally, we model the interactions of effects of class size, second language learners background, and lower socioeconomic status with these teaching techniques. We conclude that group work relates to more competency growth in math for second language learners, while classroom discussions relate to less growth for second language learners. Discussions relate to less growth in math competency for smaller classes and more growth in larger classes. Group work was also related to slower reading competency growth for children with a higher prior ability level. Findings are discussed in relation to existing theories of teaching techniques.